Electrochemically synthesized faceted CuInTe2 nanorods as an electron source for field emission applications - Lakhe, Manorama G.; Joshi, Padmshree; Choudhary, Ram J.; Ganesan, V.; Joag, Dilip S.; Chaure, Nandu B. (New Journal of Chemistry, 2018)
Herein, CuInTe2 (CIT) thin films with faceted nanorod-like morphology have been synthesized on a flexible molybdenum foil using a water-based low-cost electrodeposition technique. The co-deposition potential for CIT was optimized using cyclic voltammetry with respect to that of the Ag/AgCl reference electrode, and films were deposited from -0.6 V to -0.9 V at the working temperature of 75 degrees C. The as-prepared CIT films exhibited an amorphous nature, whereas the RTP-annealed films exhibited a highly crystalline chalcopyrite nature as a function of the growth potential. A red shift was observed in the Raman spectra of the as-deposited films that shifted towards the original position upon annealing. The Cu/In ratio obtained by the EDS analysis was found to decrease systematically upon increasing the growth potential. X-ray photoelectron spectroscopy (XPS) studies revealed the presence of Cu+, Cu2+ satellites, In3+, Te2-, and Te4+ states of Cu, In, and Te. The field emission study showed a maximum current density of 1.74 mA cm(-2), which was attainable at an applied electric field of 1.5 V mu m(-1). The turn-on field was found to be 0.92 V mu m(-1), comparable to that of the carbon nanofibres. The emitter exhibited stable electron emission over a period of 3 hours. The faceted CIT nanorods with columnar growth are a potential candidate for application as an electron source, and herein, the field emission of CIT nanorods is reported for the first time.